The social dynamics of school bullying : The necessary dialogue between the blind men around the elephant and the possible meeting point at the socialecological square - Robert Thornberg (Linköping University Electronic Press, 2015)
Bullying has over the years been examined and explained in individual as well as in contextual terms, and from a wide range of different theories and methods. A growing number of bullying researchers approach bullying as a socially complex phenomenon and from social psychological and sociological perspectives. There is today a tension between theoretical perspectives on bullying, but also a need for investigating the social and contextual aspects of bullying further. In this article, I will argue for the necessity of dialogue between different theoretical perspectives and the inclusive potential of the social-ecological framework to create a meeting point of theories in order to develop a more comprehensive understanding of school bullying.